(Not an) ambivalence toward Michelangelo in Federico Borromeo’s De pictura sacra and Musaeum - Riklius, Tomas (Literatūra, 2020)
This article discusses the role of Michelangelo Buonarroti in the Seventeenth-century art theory treatises of Cardinal Federico Borromeo De pictura sacra and Musaeum. In the referred text we can notice an ambivalent approach to the artistic genius of Buonarroti. In several cases Borromeo mentions Michelangelo as an artistic example who equalled or even exceled the great artists of Antiquity, albeit in other paragraphs the author criticises the artist for his aesthetic fallacy. A close reading of De pictura sacra and Musaeum, as well as an analysis of Borromeo’s didactic programme in the newly established Accademia del disegno in Milan allows to heed that Cardinal was rather an admirer of Michelangelo’s personality and talent. In De pictura sacra Buonarroti and other Renaissance Masters serve a rhetoric function and allow to conceptualise the theological and aesthetic framework for a post-Tridentine Catholic religious art.